Ferrous Iron and Sulfur Oxidation and Ferric Iron Reduction Activities of Thiobacillus ferrooxidans Are Affected by Growth on Ferrous Iron, Sulfur, or a Sulfide Ore - Suzuki, Isamu (1990)
Eight strains of Thiobacillus ferrooxidans (laboratory strains Tf-1 [= ATCC 13661] and Tf-2 [= ATCC 19859] and mine isolates SM-1, SM-2, SM-3, SM-4, SM-5, and SM-8) and three strains of Thiobacillus thiooxidans (laboratory strain Tt [= ATCC 8085] and mine isolates SM-6 and SM-7) were grown on ferrous iron (Fe(2+)), elemental sulfur (S(0)), or sulfide ore (Fe, Cu, and Zn). The cells were studied for their aerobic Fe(2+) - and S(0)-oxidizing activities (O(2) consumption) and anaerobic S(0)-oxidizing activity with ferric iron (Fe(3+)) (Fe(2+) formation). Fe(2+)-grown T. ferrooxidans cells oxidized S(0) aerobically at a rate of 2 to 4% of the Fe(2+) oxidation rate. The rate of anaerobic S(0) oxidation with Fe(3+) was equal to the aerobic oxidation rate in SM-1, SM-3, SM-4, and SM-5, but was only one-half or less that in Tf-1, Tf-2, SM-2, and SM-8. Transition from growth on Fe(2+) to that on S(0) produced cells with relatively undiminished Fe(2+) oxidation activities and increased S(0) oxidation (both aerobic and anaerobic) activities in Tf-2, SM-4, and SM-5, whereas it produced cells with dramatically reduced Fe(2+) oxidation and anaerobic S(0) oxidation activities in Tf-1, SM-1, SM-2, SM-3, and SM-8. Growth on ore 1 of metal-leaching Fe(2+)-grown strains and on ore 2 of all Fe(2+)-grown strains resulted in very high yields of cells with high Fe(2+) and S(0) oxidation (both aerobic and anaerobic) activities with similar ratios of various activities. Sulfur-grown Tf-2, SM-1, SM-4, SM-6, SM-7, and SM-8 cultures leached metals from ore 3, and Tf-2 and SM-4 cells recovered showed activity ratios similar to those of other ore-grown cells. It is concluded that all the T. ferrooxidans strains studied have the ability to produce cells with Fe(2+) and S(0) oxidation and Fe(3+) reduction activities, but their levels are influenced by growth substrates and strain differences.